Patents, R&D subsidies, and endogenous market structure in a schumpeterian economy. (January 2016) - Chu, Angus C.; Furukawa, Yuichi; Ji, Lei
Abstract : This study explores the different implications of patent breadth and R&D subsidies on economic growth and endogenous market structure in a Schumpeterian growth model. We find that when the number of firms is fixed in the short run, patent breadth and R&D subsidies serve to increase economic growth as in previous studies. However, when market structure adjusts endogenously in the long run, R&D subsidies increase economic growth but decrease the number of firms, whereas patent breadth expands the number of firms but reduces economic growth. Therefore, in accordance with empirical evidence, R&D subsidy is perhaps a more suitable policy instrument than patent breadth for the purpose of stimulating long‐run economic growth.